KinesioTaping after botulinum toxin type A for cervical dystonia in adult patients. Issue 4 (3rd March 2022) - Dec‐Ćwiek, Małgorzata; Porębska, Karolina; Sawczyńska, Katarzyna; Kubala, Marcin; Witkowska, Magdalena; Zmijewska, Kinga; Antczak, Jakub; Pera, Joanna
Abstract: Introduction: Studies explored physiotherapeutic approaches in cervical dystonia (CD) patients with or without botulinum toxin (BoNT) injections, however the results are varying. There are no clinical trials investigating the effects of kinesiology taping in CD patients. The objective of this study is to investigate the efficacy of kinesiology taping as an adjunct to the BoNT injections in patients with CD. Methods: Twenty‐five patients were enrolled to the study. Patients were randomly assigned to the experimental 1 (BoNT + KinesioTaping), experimental 2 (BoNT + ShamTaping) or control (BoNT) treatment. After 12 weeks they were moved to the next experimental group and finally every patient received all 3 proposed treatment options. The severity of CD was quantified with the Toronto Western Spasmodic Torticollis Rating Scale (TWSTRS) including Torticollis severity, Disability, and Pain scales. Quality of life was evaluated using Craniocervical dystonia questionnaire (CDQ4). Results: In all treatment groups, there was a significant improvement in dystonia symptoms measured with TWSTRS (total score) after BoNT injection regardless of the allocation to the experimental treatment ( p  < .05). ANOVA analysis revealed no differences in any of the TWSTRS variables after the intervention. Quality of life was significantly improved after application of taping ( p  < .05, p  = .03). Conclusions: Application of KinesioTaping after BoNT injection provided no additional effect on the severity of dystonia, although the quality of life was improved in patients with CD. Further research investigating the effect of KinesioTaping prior to BoNT injection is required. Abstract : There are no clinical trials investigating the effects of kinesiology taping in CD patients. The objective of this study is to investigate the outcome of kinesiology taping in addition to BoNT injections in patients with CD. Application of KinesioTaping after BoNT injection provided no effect on the severity of dystonia and quality of life in patients with CD.